Niger notes better food security - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
The January 2003 Niger report of the Famine Early Warning Systems Network (FEWS) says there is good access to cereal products on a household level. Harvests have been mostly plentiful and such items as groundnuts, sesame and ducks have been widely...